2013
DOI: 10.5414/cp201781
|View full text |Cite
|
Sign up to set email alerts
|

Bioequivalence study of a novel orodispersible tablet of meloxicam in a porous matrix after single-dose administration in healthy volunteers

Abstract: Test and reference formulations met the regulatory criteria for bioequivalence in the fasting healthy volunteers enrolled.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…compared the bioavailability of meloxicam after oral an orodispersible tablet (15 mg/dose) with a reference tablet in healthy human under fasting condition. They found that the test and reference formulations met the regulatory criteria for bioequivalence in terms of AUC and C max regardless of the rapid disintegration of orodispersible tablet . Similarly, Helmy and Bedaiwy investigated the impact of formulation factor on the pharmacokinetic parameters and the bioequivalence of a commercial suspension and tablet formulations of meloxicam (15 mg/dose) in male volunteers under fasting conditions .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…compared the bioavailability of meloxicam after oral an orodispersible tablet (15 mg/dose) with a reference tablet in healthy human under fasting condition. They found that the test and reference formulations met the regulatory criteria for bioequivalence in terms of AUC and C max regardless of the rapid disintegration of orodispersible tablet . Similarly, Helmy and Bedaiwy investigated the impact of formulation factor on the pharmacokinetic parameters and the bioequivalence of a commercial suspension and tablet formulations of meloxicam (15 mg/dose) in male volunteers under fasting conditions .…”
Section: Discussionmentioning
confidence: 99%
“…They found that the test and reference formulations met the regulatory criteria for bioequivalence in terms of AUC and C max regardless of the rapid disintegration of orodispersible tablet. [16] Similarly, Helmy and Bedaiwy investigated the impact of formulation factor on the pharmacokinetic parameters and the bioequivalence of a commercial suspension and tablet formulations of meloxicam (15 mg/dose) in male volunteers under fasting conditions. [17] They concluded that a single oral administration Table 3 Pharmacokinetic parameters for meloxicam formulation including R (Mobic â ), products A and B (data were shown as mean AE SD, n = 9) of the suspension formulation met comparable clinical outcomes as compared with the reference tablet.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, increasing attention has been paid to the PK of meloxicam. 16,17 However, few studies have been performed in Chinese HVs. 18,19 This study, with fasting and fed arms, was performed to investigate the BE of meloxicam from 2 manufacturers.…”
Section: Discussionmentioning
confidence: 99%